Accommodating the expressive function of victim impact statements: the scope for victims’ voices in Dutch courtrooms - Booth, Tracey (The British journal of criminology, 2018)
The expressive function of victim impact statements (VISs) enables victims to have a voice in legal proceedings—to speak and be heard about the harm caused by the offence. VISs have been adopted in many jurisdictions. While research reveals legal and institutional constraints on the expressive function of VISs in many jurisdictions with adversarial proceedings, we know little about the implementation of VISs in inquisitorial systems. We address this gap by reporting findings of an observational study that examines the scope for victims’ voices in criminal legal proceedings in the Netherlands. We find that these proceedings are better adapted to accommodate the expressive function of VISs. There is greater scope for victims to speak and be heard through their VISs.